Marine Biological Investigations of Jørgen Brønlund Fjord, North Greenland. - Just, Jean (Meddelelser om Grønland, 1970)
The topography, geology, and climatic conditions around Jørgen Brønlund Fjord, North Greenland are briefly outlined. The ice conditions as found in the summer of 1966 are described, together with a survey of observations on the ice since 1947. Based on the bathygraphy and the different types of bottom sediments, the fiord is divided into five regions: estuary, inner basin, threshold, outer basin, and Kap Harald Moltke region. Hydrographical data collected in 1966 are presented. The zonation of marine algae in the fiord is mentioned. Methods discussed include the blasting of limited holes for sampling through sea ice 2.5 m. thick. Lists of sampling stations from the First, Third, and Fourth Peary Land Expeditions are given.